Evidence-informed policymaking and policy innovation in a low-income country: does policy network structure matter?. (31st August 2018) - Shearer, Jessica C; Lavis, John; Abelson, Julia; Walt, Gill; Dion, Michelle
Abstract : The application of social network analysis to policy networks continues to grow, including the application of social network analysis tools and concepts in order to explain policy outcomes. Gaps in this field of study persist in terms of both policy issues studied, as well as types of polities or networks analysed. This study extends previous research on the role of network structure in shaping policy outcomes by analysing network structure's effect on the use of research evidence by three health policy networks in Burkina Faso, a low-income West African country, and the resulting innovativeness of the policies made. This comparative case study confirms certain hypotheses related to the effect of network closure and heterogeneity on evidence use and innovation; namely, that heterogeneous networks are more likely to be exposed to new ideas, and thus to use research evidence and adopt innovative policies. High levels of centralised control and power may support innovation when the new ideas are consistent with the dominant network paradigms; otherwise, new ideas may receive less traction. These findings confirm previous research and point to opportunities to shape networks to achieve innovation and policy change based on the best evidence.